High-dimensional single-cell cartography tracking of immune cells subpopulation of mice peripheral blood treated with gold nanorods and black phosphorus nanosheets. (December 2022) - Cheng, Mo; Shi, Hongtao; Xu, Tianzhao; Jiang, Wei; Tang, Ben Zhong; Duo, Yanhong
Abstract: The gold nanorods (Au NRs) and black phosphorus nanosheets (BP NSs) are one of the commonly investigated nanomaterials (NMs) that substantially promoted biomedical nanotechnology. Recently, NMs-based immunotherapies have been a hot research focus in various fields, and some studies have revealed their immunotoxicity. However, their effects on the immune system are still overlooked, making it necessary to assess their impact on immune cells entirely. A challenge in evaluating the immunotoxicity of NMs is tracking the subpopulation of immune cells at single-cell level. Therefore, we applied the cytometry by time-of-flight (CyTOF) that exhibied an unparalleled ability to phenotypically and functionally profile complex cellular subpopulations using multiple panels (42 immune markers) to analyze the change of immune cells subpopulation in peripheral blood after treated with Au NRs and BP NSs. As a proof of concept, the analysis showed that both NMs induced significant changes of almost immune cell subpopulation in peripheral blood, which perturbates the innate and adaptive immune responses significantly. The work revealed not only the immunotoxicity of NMs but also guided the application of NM-based strategies and might facilitate further understanding of their toxicology. Graphical Abstract: Schematic diagram of the immune cell mapping of mice peripheral blood on gold nanorods and black phosphorus nanosheets. ga1 Highlights: Au NRs induces significant alteration of immune cells in peripheral blood. BP NSs induces significant alteration of immune cells in peripheral blood. The Au NRs and BP NSs exhibit obvious long term immunological effects.